Social Media and Mental Health Amid Corona Virus Pandemic - A.Nur Aisyah Rusnali (Palakka : Media and Islamic Communication, 2020)
Abstract:The purpose of this study was to determine how the use of social media during the COVID-19 pandemic and what social media had to do with mental health during the COVID-19 pandemic. The research method used in this study is the research library, which is considered effective during the COVID-19 emergency status. Social media is one way that is considered effective to overcome the boredom of being at home. Social media can keep us connected with people who are separated from us. However, the use of social media must be fortified with knowledge and wise thoughts, because not all information we receive through social media is true. We cannot panic quickly with the information we get. We should first check the information we receive. This is very important to do to maintain our mental health during the COVID-19 pandemic. Keywords: Social Media; Mental Health; COVID-19.